The Design and analysis of industrial experiments - Box, George E. P.; Davies, Owen L. (New York: Published for Imperial Chemical Industries by Longman Group, 1978)
The planning of simple comparative experiments; Sequential tests of significance; Investigation of sampling and testing methods; Randomized blocks and latin squares; Incomplete randomised blocks design; Factorial experiments: elementary principles; Factorial experiments with factors at more than two levels; Confouding in factorial designs. Factorial experimentation when uniform conditions cannot be maintained throughout the experiment; Fractional factorial experiments; The determination of optimum conditions.
Introduction -- the Planning of simple comparative Experiments -- Sequential Tests of Significance -- Investigation of Sampling and Testing Methods -- Randomized Blocks and Latin Squares -- Incomplete Randomised Block Designs -- Factorial Experiments: Elementary Principles -- Factorial Experiments with Factors at more than two levels -- Confounding in Factorial Designs. Factorial Experimentation when Uniform conditions can not be Maintained throughout the experiment -- Fractional Factorial Experiments -- The determination of Optimum conditions
Includes glossary and indexes.
Keywords: Statistics; Design of Experiments; Design and Analysis